Schizophrenia and substance use - Akvardar, Yıldız; Tümüklü, Mevhibe; Alptekin, Köksal (Journal of Dependence, 2003)
Although many studies reported that approximately half of the patients with schizophrenia are also substance abusers at some time during their lives, there is yet no consensus on the prevalence of substance abuse comorbidity in schizophrenia. Alcohol dependence, smoking and psychostimulant abuse are three most frequently reported addictions in schizophrenia. Various hypotheses, such as genetic vulnerability, neurodevelopmental pathologies, supersensitivity, self medication, social-enviromental factors, personality characteristics have been suggested to explain the reasons of substance use in patients with schizophrenia. Although the current pervasiveness of this problem may partially be due to an increasing acceptability of substance use in society and substance availability, as well as the deinstitutionalization of psychiatric treatment, the exact mechanisms contributing to comorbid substance abuse in schizophrenia have not clarified yet. Relatively high prevalence of cigarette smoking and alcohol use and neglectable rates of illegal substance use in our country compared to other countries provide support that exposure and access to substances play a major role in comorbidity of substance use disorders in schizophrenia. This paper reviews some unclarified main issues on this subject despite the recent studies and summarizes the results of the studies done in our country.
Keywords: Schizophrenia; substance use; substance abuse